Harassment and Burnout in Academic Pediatric Anesthesiology - Walker, K. Karisa; Reddy, Srijaya K.; Deutsch, Nina; Agarwal, Rita; Glass, Nancy L.; Cladis, Franklyn P. (Pediatric anesthesia, 2025)
ABSTRACT Background High‐profile cases of sexual harassment (SH) have drawn attention to SH in the workplace via the #MeToo movement. Many studies demonstrate SH occurring in medical training and practice. Experiencing SH correlates with long‐term personal and professional detrimental effects. Aims We sought to identify the prevalence of SH among pediatric anesthesiology fellowship program directors (PDs), associate PDs (APDs), and fellows. For comparison, we collected data about exposure to nonsexual harassment (NSH). We assessed the relationship between SH and burnout, characteristics of which overlap with documented ramifications of SH. We hypothesized our participants would report a high rate of SH, which would in turn correlate with higher levels of burnout. Methods The Maslach Burnout Toolkit (MBT) and a sexual harassment survey were sent to PDs (n = 60) of pediatric anesthesiology fellowships to complete and distribute to APDs and fellows (~221). Results were analyzed using descriptive statistics, Chi‐square test, and Fisher's exact test. Results One hundred and sixty‐three physicians completed the surveys: 41 PDs, 13 APDs, and 109 fellows. Twenty‐two percent of respondents had experienced SH, 28% had witnessed SH, and 42% had experienced NSH. PDs were more likely to have experienced or witnessed SH or NSH than fellows (p < 0.05). Women were more likely to experience or witness SH. Those who experienced SH were more likely to report depersonalization (p < 0.05). Those who experienced or witnessed NSH were more likely to report emotional exhaustion and depersonalization (p < 0.05). Perpetrators of harassment were reported most commonly to be male surgical attendings. Conclusion Harassment at work is common and may contribute to burnout among pediatric anesthesiologists. Lower incidence of SH among fellows suggests the work environment may be improving with time, but there is still work to do to ensure a safe environment for pediatric anesthesiologists.